2019
DOI: 10.1039/c9mh00495e
|View full text |Cite
|
Sign up to set email alerts
|

Bionic synthesis of a magnetic calcite skeletal structure through living foraminifera

Abstract: This communication describes the bionic preparation of a composite material in which fluorescent magnetite nanoparticles are included within the calcitic skeletal structure of the foraminifer Amphistrigina lessoni.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Recently, calcite skeletal structures of marine protozoa foraminifera have been used for the synthesis of magnetic nanocomposites. This is, the first report of bionic synthesis of nanocomposites using the natural biomineralization pathway ( Magnabosco et al, 2019 ). Other studies have reported the biosynthesis of QDs by Tetrahymena pyriformis .…”
Section: Protozoans As Cellular Factories For Nanomaterials Synthesismentioning
confidence: 93%
“…Recently, calcite skeletal structures of marine protozoa foraminifera have been used for the synthesis of magnetic nanocomposites. This is, the first report of bionic synthesis of nanocomposites using the natural biomineralization pathway ( Magnabosco et al, 2019 ). Other studies have reported the biosynthesis of QDs by Tetrahymena pyriformis .…”
Section: Protozoans As Cellular Factories For Nanomaterials Synthesismentioning
confidence: 93%
“…A recent work described the in vivo preparation of a bionic material through the inclusion of fluorescent magnetite nanoparticles within calcite skeletal structure of the unicellular organism foraminifer Amphistrigina lesson. Such in vitro synthetic approach exploited the natural biomineralization process of growth in the presence of magnetic nanoparticles functionalized with a hydroxylated dextran shell [106].…”
Section: Cell Culture Conditionsmentioning
confidence: 99%
“…The conditions used in these synthetic protocols are usually harsh and employ elevated temperatures and pressures, organic solvents and toxic and expensive chemicals. Living organisms can offer great assistance to chemists to synthesize new materials (Valentini et al, 2016;Ashfaq et al, 2018;Nguyen et al, 2018;Magnabosco et al, 2019;Pugno and Valentini, 2019). After all, living organisms are essentially "nano-factories."…”
Section: Introductionmentioning
confidence: 99%